Short-Crested Wave–Current Forces on a Concentric System with an ARC Exterior Porous Wall - Jianming Miao; Dan Liu; Jie Li; Zhenfeng Zhai (Journal of Marine Science and Engineering, 2023)
In this study, the potential flow theory is adopted to develop an analytical solution to the diffraction problem of a short-crested wave–current incident on a concentric system consisted of an arc exterior wall and interior cylinder. The influence of the uniform current on the hydrodynamic performance of the concentric structure is primarily discussed. The incident angle and speed of the uniform current significantly influence the short-crested wave force and run-up on the concentric structure. Specific parametric conditions are obtained, under which the wave structure can resonate, and the resonance phenomenon may be more pronounced when the wave and current have the same incidence direction. Furthermore, semi-enclosed structures are highly sensitive to the direction of wave incidence, thereby triggering certain limitations in engineering applications. This study is expected to contribute as theoretical guidance to nearshore architecture designs.